Morphological, functional and biochemical differences in cardiac adaptation to endurance exercise among male and female amateur marathon runners - Lasocka-Koriat, Zofia; Lewicka-Potocka, Zuzanna; Kaleta-Duss, Anna; Bulman, Nikola; Marciniak, Ewelina; Kalinowski, Leszek; Lewicka, Ewa; Dąbrowska-Kugacka, Alicja (Frontiers in Physiology, 2025)
IntroductionSport is known to have beneficial influence on cardiovascular system. However, activities of high intensity such as marathon running may adversely affect cardiac morphology and function, especially in the heterogenous group of amateur athletes. As males and females exhibit discrepancies in cardiac response to training, we aimed to compare exercise-induced myocardial alterations between sexes among 61 amateur marathon runners, with the use of evolving echocardiographic techniques and cardiac biomarkers.MethodsThe study followed three stages: 2–3 weeks prior the marathon (Stage 1), at the finish line (Stage 2) and 2 weeks after the run (Stage 3). Echocardiographic examination along with blood analyses for biomarkers of cardiac injury and overload [creatine kinase, high sensitivity cardiac troponin I, heart-type fatty acid binding protein, B-type natriuretic peptide, galectin-3 (Gal-3), endothelin-1 (ET-1), interleukin-6 and neopterin] were performed at each stage.ResultsAfter the marathon there was a transient increase in right ventricular (RV) size and concomitant decrease in left ventricular (LV) volumes, leading to a significant increase of RV end-diastolic volume (RVEDV)/LVEDV ratio (0.91 ± 0.21 vs. 1.10 ± 0.22, p < 0.001 in males; 0.73 ± 0.17 vs. 1.02 ± 0.22, p < 0.001 in females). Although at Stage 2 RV contractility decreased, while LV ejection fraction (LVEF) remained at the same level in both sexes, men had greater tendency for LVEF reduction (p < 0.05 for the interaction sex and stage). The concentrations of biomarkers were higher after the run in both study groups, except for ET-1 and neopterin, which increased post-race only in males. The larger training-related rise in Gal-3 level correlated with the greater drop in LVEF at Stage 2 (r = −0.42; p < 0.05). Less-trained marathoners with lower VO2max values after the race showed higher levels of Gal-3 post-run (r = −0.29; p < 0.05).ConclusionMarathon running induces transient cardiac remodelling, more pronounced in male than female athletes. Structural and functional changes assessed by echocardiography correspond with biochemical alterations. Galectin-3 was the best biomarker to reflect overload changes. Cardiovascular screening in amateur runners should be implemented to identify subjects requiring further evaluation.